Mount Airy High School cheerleaders at a basketball game against Griffith High School, 1956. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 3-3-56 p.10.
Mount Airy High School cheerleaders at a basketball game against Griffith High School, 1956.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth